Fazio-Londe Syndrome and Patient-centered Nursing Care: A Case Report - Mohammad Abdi; Maryam Jolfaei; Maryam Ghasemi; Mohammad Reza Dinmohammadi; Hojjat Torkmandi; Elmira Khademi (Iran University of Medical Sciences, 2020)
Introduction: Fazio-Londe disease is a genetic rare disorder manifesting by acute respiratory distress. This article is a case report of Fazio-Londe syndrome, its comparison with other case reports in the literature, and its patient-centered nursing care.  Case presentation: In this study, we reported a case with Fazio-Londe syndrome with respiratory distress, bulbar palsy, muscle weakness, and other symptoms.  Management and outcome: The patient was treated with oral riboflavin (100 mg/day), ribavirin (200 mg/day), and intramuscular Vit-B12 (1000 mg/day). She was managed using a patient-centered nursing care model.  Discussion: Health care providers should be aware of the new and constant symptoms of this rare disease. A patient-centered nursing care model is suggested to manage the disease.